(untitled) (Journal of the College of Languages (JCL), 2018)
המחקר מתייחס לתופעת ההקטנה משני ענפים את הסימנטיקה והמורפופונולוגיה בשפה העברית, ומנסה ליגלוי את המשמעות בתוך ההקשר של צורות ההקטנה לדוגמאות מן התורה טקסטים מחדשות, שירה וסיפורים, הרי שחלק מהמשמעויות של מבנה הפלט עומדות בניגוד למשמעויות הבסיס או הדרגה במשמעות, כך מביעות על (הקטנה, חיבה, או זלזול) שרובן לא התקיימו בעברית הקלאסית, מצד אחר המחקר בדק במבנים המורפולוגיים במייוחד (המשקלים של צורת ההקטנה) ומבחין את הסיומות שחדרו לעברית משפות לועזיות למטרה זו, יתר על כן המחקר שופך את האור על המערכת הפונולוגית והשפעתה על מבנה צורת ההקטנה כדי להבהיר את התופעות החלות במבנה הפלט, ששולט בהן אלמנטים פונולוגיים כגודל המילה, המבנה הפרוזודי של המילה, והמערכת הסגמנטלית. השפה העברית המודרנית שונה משאר השפות שמקטינות את שמות התואר בלבד, על כן, בעבודה זו נקבעו צורות ההקטנה של השמות והפעלים במיוחד (הפעלים המרובעים הכפולים), וכך גם נקבעו את מטרות צורת ההקטנה בדרך כלל Abstract The paper deals with Diminutives in Hebrew at two levels: the sematic and the morpho-phonological so as to investigate the contextual meaning when forming the diminutive of a word in samples form Torah , Mishnah, and some examples of poetry and story-telling. The resulting word expresses sometimes a different or a contradictory meaning of the original word which may expresses smallness, endearment, pejorativeness or grading of meaning, where most of these have not been used in Old Hebrew, this is on one hand. On the other, the paper shows the morphological patterns, specifically those of diminutives, and pointed out the suffixes that have come into Hebrew from other languages. Along this, the paper sheds light on the phonological oatterns and their effects in diminutive forms so as to make clear the phenomena accompanying the resulting word where it is being controlled by a number of phonological aspects, such as its length, its extra-syllable structure, and its syllable structure. What distinguishes Modern Hebrew is that is different from other languages which forms diminutives form adjectives only. Therefore, the paper has pinpointed the ways of forming diminutives in Hebrew from nouns, adjectives, and verbs, more specifically, quadri-literal doubled verbs, along with specifying the purposes behind diminutives in general.